The Role of Motivation, Promotion and Religiosity on Customer Decisions to Use Savings with Trust as an Intervening Variable - Ratih Pratiwi; Donny Dharmawan; M. Anwar; Elfis Mus Abdul; Loso Judijanto (Yayasan Riset dan Pengembangan Intelektual, 2023)
Today, competition in banking sectors has been very tight, in order the banks can survive they have to provide excellent services. Besides, they should also pay attention to the promotion activity and religiosity aspect so that they can attract customers. Bank Muamalat is a company engaged in the field of Islamic banking that serves deposits in the form of savings and time deposits and distributes sharia-managed financing located in East Lombok Regency. One of the savings products available at Bank Muamalat KK Mataram-Masbagik is iB Hijrah Plan product. This study aims to analyze and examine the factors influencing the motivation, promotions and religiosity on customer decisions with trust as an intervening variable in Bank Muamalat KK Mataram-Masbagik. The method of research is using the quantitative and regression analysis. The sampling technique used an accidental sampling. The sample used as the research object was customer's registered at Bank Muamalat KK Mataram-Masbagik so that 60 respondents were obtained. The data was analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). Based on the analysis, the research shows that the religiosity has a significant positive effect on customer decisions, while motivation and promotion do not have a significant effect on custome's decisions to use the iB Hijrah Plan at Bank Muamalat KK Mataram-Masbagik. The trust is able to mediate the influence of promotion and religiosity on customer decisions, while the trust is unable to mediate the influence of motivation on customer's decisions to use the iB Hijrah Plan. This study contributes to Bank Muamalat KK Mataram-Masbagik so that it maintains aspects of customer trust. If customer trust in Bank Muamalat KK Mataram-Masbagik continues to increase, then customers will not turn to other sharia banks and will continue to use the services provided.